On the stability of neutral-type uncertain systems with multiple time delays - Liu, Pin-Lin (Zielona Góra: Uniwersytet Zielonogórski)
The problems of both single and multiple delays for neutral-type uncertain systems are considered. First, for single neutral time delay systems, based on a Razumikhin-type theorem, some delay-dependent stability criteria are derived in terms of the Lyapunov equation for various classes of model transformation and decomposition techniques.
Keywords: Razumikhin-type theorem; time-delay; neutral type uncertain systems